Medical Liability for Allocation of Scarce Healthcare Resources in the COVID-19 Pandemic: the Italian scenario - Foglia Massimo (Wroclaw Review of Law, Administration and Economics, 2022)
1. Tragic Choices in COVID times; 2. Criteria for the Allocation of Scarce Healthcare Resources; 3. Liability of Healthcare Professionals and Institutions; 4. Possible solutions?